65 kHz picosecond digital off-axis holographic imaging of 3D droplet trajectory in a kerosene swirl spray flame. (January 2023) - Wang, Lei; Li, Tianxiong; Zhao, Yue; Zhang, Hang; Wu, Yingchun; Song, Ge; Liu, Tao; Wu, Xuecheng
Highlights: 65 kHz pulsed digital off-axis holography is proposed to measure kerosene size and velocity in swirl spray combustion field. Particle matching method considering the x, y, z, and diameter with different measurement errors is proposed. Smoothed trajectories of fuel droplets in the combustion field are obtained and analyzed. Abstract: It is difficult to track fuel droplets in a swirl spray combustion field due to three-dimensional (3D) movement and turbulent flame influence. The present work carries out an experimental study to investigate and track the dispersed kerosene droplets in a swirl spray combustion field. RP-3 kerosene and air are mixed and burned in open space under different mixture ratios. Pulsed high-speed (65 kHz) digital off-axis holography with an equivalent pixel size of 9.3 μ m is adopted to visualize and quantify the droplet size, 3D position and velocity. The measurement uncertainty of the technique is calibrated and discussed. The turbulent flame of hydrocarbon fuel causes some darker speckles in the morphology view, but droplet images are clear and the initial droplet size distribution at 1 mm downstream of the swirler is obtained. A particle tracking algorithm considering x, y and z with different locating errors and droplet diameter is proposed and applied to obtain droplet trajectory. Smoothed droplet trajectories are obtained through multi-frame tracking and trajectory regressing methods. From the perspective of the Lagrangian view, droplet momentum and size oscillation are also observed and discussed.